Peran Literasi Perpajakan: Determinan Kepatuhan Wajib Pajak Pelaku UMKM Sektor Industri Kreatif Di Kota Yogyakarta - Inna Zahara; Damara, Danu (LPPM Universitas Pelita Bangsa, 2025)
This study aims to determine the influence of external factors consisting of the use of information technology, tax administration reform, and tax sanctions as well as internal factors, namely tax literacy as a moderator of taxpayer compliance of MSME actors in the creative industry sector in the city of Yogyakarta. This research approach involves collecting data through structured instruments that measure respondents' responses on a certain scale. Data analysis was carried out by statistical methods to test the relationship of variables and the role of moderation factors. The test results show that the variables of information technology utilization and tax administration reform have an effect on taxpayer compliance. The tax sanction variable has no effect on taxpayer compliance, partially the tax literacy variable is unable to moderate the influence of the variable of information technology utilization and tax sanctions on the taxpayer compliance variable. However, the tax literacy variable is able to moderate the influence of the tax administration reform variable on the taxpayer compliance variable.